Can interface charge enhance selectivity in tunnel layer passivated contacts? Using negatively charged aluminium oxide capped with dopant free PEDOT or boron doped polysilicon - Kaur, G (Elsevier BV, 2020)
10.1016/j.solmat.2020.110857